ANALYSIS OF GOVERNMENT POLICY IN HOSPITAL ACCREDITATION THROUGH HEALTH MINISTER REGULATION NUMBER 12 OF 2020 - Widjayanto, Indra (LPPM Univ. Ibn Khaldun Bogor, 2024)
The Minister of Health's Regulation Number 12 of 2020 concerning Hospital Accreditation aims to improve the quality of health services by establishing minimum standards that hospitals must meet. However, the implementation of this regulation is still considered suboptimal and has numerous shortcomings. This study aims to further analyze the advantages and disadvantages of the implementation of these regulations. This research employs the normative juridical research method. The normative juridical research method involves conducting library research, scrutinizing library materials or secondary data, and referencing the laws that govern hospital accreditation, particularly the Minister of Health Regulation Number 12 of 2020. The study's results suggest that the Regulation of the Minister of Health Number 12 of 2020 concerning Hospital Accreditation offers several advantages, including enhanced quality standards, information disclosure, an objective assessment process, improved hospital management quality, and a focus on patient safety. The shortcomings of the Minister of Health Regulation Number 12 of 2020 concerning hospital accreditation include administrative burdens, high implementation costs, resource gaps, the risk of focusing on processes, and regulatory changes. The proposed recommendations aim to address the shortcomings of the Minister of Health Regulation Number 12 of 2020 concerning hospital accreditation. These include reducing administrative burdens, overcoming high implementation costs, reducing resource gaps between hospitals, ensuring a focus on end results in services, and reducing uncertainty in regulatory changes.